Self-perceived functioning in relation to existing symptoms 12 months after SARS-COV-2 infection in workers of an industrial facility in Aveiro Region – an observational study. Functioning in relation to symptoms 12 months after SARS-COV-2 infection - Pádua, Ana R. (2023)
Background/Objective: Most individuals recover after acute SARS-CoV-2 infection, but some may suffer persistent symptoms with potential medium and long-term consequences. The present study aims to analyze self-perceived functioning concerning existing symptoms 12 months after SARS-CoV-2 infection in workers of an industrial facility in the Aveiro Region. Methods: Observational study, including workers with a positive SARS-CoV-2 RT-PCR/TRAg test. After 12 months of the infection, the occupational health team collected information on sociodemographic variables, manifested symptoms, and perceived functioning assessed using the WHODAS-2.0–12 items - where '12 points' means the highest functioning. Data analysis included descriptive statistics and univariate and multivariate linear regression. Results: Eighty-five workers were infected with SARS-CoV-2, 77.7% were male, with a mean age of 36y1m±9y8m, 36.8% have a higher education level and 17.7% reported at least one chronic condition. Thirty workers (35.3%) reported persistent symptoms, with fatigue (27.7%) and arthralgia (14.4%) being the most described. Whodas 2.0 mean score was 15,7±5,0, and items most frequently reported as presenting limitations were difficulties in working (43.5%), concentrating (35.3%), and walking one kilometer (35.3%). Self-perceived functioning depended on educational level (β=-2.37, CI95% -4.53 ; -0.21) or the existence of a chronic illness (β=3.53, CI95% 0.81 ; 6.24), and the level of functioning is associated with the persistence of symptoms of fatigue (β=4.02, CI95% 1.75 ; 6.29), headache (β=4.13, CI95% 0.84 ; 7.42), and myalgia (β=3.30, CI95% 0.14 ; 6.45). Conclusions: Persistent symptoms 12 months after symptomatic SARS-CoV-2 infection have an influence on self-perceived functioning. Occupational health services should regularly address the assessment of persistent symptoms of SARS-CoV-2 infection to prevent possible impacts on daily activities and participation.